Reconstructing The Role of Confiscation and Seizure in Realizing The Right to Restitution for Victims of Criminal Acts - Ubwarin, Erwin; Nelson, Febby Mutiara; Jatna, R Narendra; Soplantila, Valentino Dinatra (LAW REFORM, 2026)
The National Criminal Code (KUHP) and Law No.20 of 2025 concerning the Criminal Procedure Code (KUHAP) have strengthened the recognition of victims’ rights, particularly with regard to restitution as an additional punishment. In practice, however, restitution has not been implemented optimally, resulting in many victims failing to obtain adequate compensation. The aims of this study are: 1) to identify and analyse the role of conventional seizure as evidence, and 2) to analyse and formulate the role of modern seizure as an instrument for restoring victims’ rights. Employing a doctrinal approach, this research produces descriptive legal analysis and prescriptive recommendations by formulating an expanded concept of seizure. The findings indicate that both the KUHP and the KUHAP regulate restitution as a victim’s right to material and immaterial compensation and recognise seizure as a legal instrument. However, there is no explicit regulation linking seizure directly to the fulfilment of restitution. Consequently, restitution remains difficult to enforce when perpetrators lack assets or refuse to comply. The study concludes that the concept of seizure must be expanded to include the broader seizure of perpetrators’ assets and the possibility of state-funded compensation to ensure that victims’ restitution rights are realised effectively, fairly and enforceably.